Strengthening New Infrastructure Assets : A Cost-Benefit Analysis - Hallegatte, Stephane (World Bank, Washington, DC, 2019)
This paper explores the benefits and the costs of strengthening infrastructure assets to make them more resilient, reducing the repair costs and infrastructure disruptions caused by natural hazards. Strengthening infrastructure assets in low- and middle-income countries would increase investment needs in power, transport, and water and sanitation by between $11 billion and $65 billion a year, i.e. 3 percent of baseline infrastructure investment needs. The uncertainty pertaining to the costs and benefits of infrastructure resilience makes it difficult to provide a single estimate for the benefit-cost ratio of strengthening exposed infrastructure assets. To manage this uncertainty, this paper explores the benefit-cost ratio in 3,000 scenarios, combining uncertainties in all parameters of the analysis. The benefit-cost ratio is higher than 1 in 96 percent of the scenarios, larger than 2 in 77 percent of them, and higher than 4 in half of them. The net present value of these investments over the lifetime of new infrastructure assets -- or, equivalently, the cost of inaction -- exceeds $2 trillion in 75 percent of the scenarios and $4.2 trillion in half of them. Moreover, climate change makes the strengthening of infrastructure assets even more important, doubling the median benefit-cost ratio.